Mastering your PhD survival and success in the doctoral years and beyond - Gosling, Patricia 1963-; Noordam, Lambertus D.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Mastering Your PhD: Survival and Success in the Doctoral Years and Beyond helps guide PhD students through their graduate student years. Filled with practical advice on getting started, communicating with your supervisor, staying the course, and planning for the future, this book is a handy guide for graduate students who need that extra bit of help getting started and making it through. While mainly directed at PhD students in the sciences, the book's scope is broad enough to encompass the obstacles and hurdles that almost all PhD students face during their doctoral training. Who should read this book? Students of the physical and life sciences, computer science, math, and medicine who are thinking about entering a PhD programme; doctoral students at the beginning of their research; and any graduate student who is feeling frustrated and stuck. It's never too early -- or too late! This second edition contains a variety of new material, including additional chapters on how to communicate better with your supervisor, dealing with difficult people, how to find a mentor, and new chapters on your next career step, once you have your coveted doctoral degree in hand
1 Choosing a research group : pluses and pitfalls 2 Getting started 3 Setting goals and objectives 4 How to think like a scientist 5 Designing good experiments 6 Charting your progress month by month 7 Dealing with setbacks 8 Mentors, leadership, and community 9 How to get along with your lab mates, et al. 10 Group dynamics : dealing with difficult colleagues 11 The art of good communication 12 Mastering presentations and group meetings 13 Searching the scientific literature 14 Your first international conference 15 From data to manuscript : writing scientific papers that shine 16 Celebrate your success 17 How to make the best of your annual evaluation 18 The final year : countdown to your thesis defence 19 Writing your doctoral thesis with style 20 The final act : defending your thesis with panache 21 Putting it all together : a PhD- so what?s next? 22 Is industry right for you : opportunities to explore 23 Exploring not-for-profit organizations 24 Lessons learned
Electronic reproduction
Keywords: Doctor of philosophy degree -- Handbooks, manuals, etc; Graduate students -- Handbooks, manuals, etc; Universities and colleges -- Graduate work -- Handbooks, manuals, etc; Study skills -- Handbooks, manuals, etc; Promotion